ELICITIATION OF INFORMATICS ENGINEERING INFOTECH WEBSITE NEEDS USING A USER PERSONA APPROACH - Abd. Saleh; Wahyu Andhyka Kusuma (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2023)
Requirements elicitation is the most important activity in the software development process, because it has a direct impact on the success of the development process. The success of a software is determined from the involvement of a user persona at the design stage. The involvement of user personas in software design is critical in the requirements engineering process, because if the process is done incorrectly, the resulting software will also have poor quality. This study focuses on using the approach of the user persona in collecting information related to the needs of the informatics engineering infotech website at the University of Muhammadiyah Malang, so that the results obtained can be in accordance with the needs of the user. The final result that is expected in this research is a design of the plagiarism check feature for the practitioner's program automatically on the infotech website which is implemented in the form of use cases and prototypes. This feature will later make it easier for assistants in assessing program results collected by practitioners, so that the time needed to correct the program can be done faster.